Povestirea vieții – identitate și alteritate pe parcursul Războiului civil elen din 1946-1949 / LIFE HISTORIES – IDENTITY AND ALTERITY DURING THE GREEK CIVIL WAR OF 1946 – 1949 - Gabriela Boangiu (Incursiuni în imaginar, 2017)
The study tries to highlight the processes of identification and diferentiation which produce identity or alterity in the context of the transfer of numerous children from Greece to Romania through the mediation of the Red Cross, and also in the context of the story of a young – at that time, soldier during the Greek civil war (1946-1949);he was wounded and got healed in Romania. At the begining, the study will present a few indications on how to built a collection of life histories, then we will refer strictely to identity and alterity in life histories.